2004
DOI: 10.1103/physreva.69.013813
|View full text |Cite
|
Sign up to set email alerts
|

Entangled light in transition through the generation threshold

Abstract: We investigate continuous variable entangling resources on the base of two-mode squeezing for all operational regimes of a nondegenerate optical parametric oscillator with allowance for quantum noise of arbitrary level. The results for the quadrature variances of a pair of generated modes are obtained by using the exact steady-state solution of Fokker-Planck equation for the complex Pquasiprobability distribution function. We find a simple expression for the squeezed variances in the near-threshold range and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Application of this method for the numerical study of open quantum-optical systems are shown, in particular, in the works [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Detailed analysis of this three-photon radiation process in case of monochromatic pump field ( ) 1 f t = is presented in the work [16].…”
Section: K a A A Amentioning
confidence: 97%
“…Application of this method for the numerical study of open quantum-optical systems are shown, in particular, in the works [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Detailed analysis of this three-photon radiation process in case of monochromatic pump field ( ) 1 f t = is presented in the work [16].…”
Section: K a A A Amentioning
confidence: 97%
“…[46] Therefore, the operator can be approximated near the steady-state value as: O = O s + 𝛿O, where O = a i , m, b, with O s representing the mean value of O and 𝛿O denoting the fluctuation of O. After we substitute the approximate operator to QLE, we can easily obtain steady-state solution considered in the monostable region [47] a 1s = −𝜀 1…”
Section: Model and Hamiltonianmentioning
confidence: 99%
“…[ 46 ] Therefore, the operator can be approximated near the steady‐state value as: O=Os+δO$O=O_s+\delta O$, where O=ai,m,b$O=a_{i}, m, b$, with Os$O_s$ representing the mean value of O$O$ and δO$\delta O$ denoting the fluctuation of O$O$. After we substitute the approximate operator to QLE, we can easily obtain steady‐state solution considered in the monostable region [ 47 ] a1s=ε1(itrueΔa1+κa1)+iε2Jfalse(inormalΔa1+κa1false)false(Δm+κmfalse)ε1J2false(iΔm+κmfalse)Ma2s=ε1+(itrueΔa1+κa1)a1siJms=ig2a2sfalse(iΔm+κmfalse)…”
Section: Model and Hamiltonianmentioning
confidence: 99%
“…The application has been constructed on the base of the numerical simulation method of quantum trajectories or Quantum State Diffusion (QSD) method [3]. The corresponding library includes investigation of quantum dissipative chaos, bistability and bifurcations [4][5][6][7][8], quantum stochastic resonance [9], long-lived quantum interference in periodically modulated oscillatory systems [10], engineering of Fock states and qubits in nonlinear oscillators [11] elaboration of devices generating intensive entangled light beams for quantum communications [12][13][14][15] as well as production of threephoton entangled states in parametric devices [16][17][18] and numerical simulation of complex quantum optical systems (see, particularly, interaction of an atom with bichromatic laser field [19][20][21], cascaded processes [22] and photonics in ion-trap systems [23]).…”
Section: Introductionmentioning
confidence: 99%
“…The density operator using an expansion of the state vector  in a truncated basis of Fock's number states of a harmonic oscillator (photonic states) is calculated. In this way, the ECAQT library corresponding to QSD method has been applied for various physical problems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%